Islamic Values and Morality in The Hikayat Nabi Isa Manuscript: A Textual Study - Saefullah, Muhammad Iqbal; Wirajaya, Asep Yudha; De Jesus, Isac Da Costa; Ahmad, Waqas (Analisa: Journal of Social Science and Religion, 2024)
A text within literary works does not emerge from cultural and traditional voids. Islamic literary works such as hikayat play a role in conveying spiritual, moral, and religious values to the Malay-Archipelago community of that era. The objective of this research is to elucidate the Islamic values and moralities within the ancient manuscript of Hikayat Nabi Isa that remains relevant within the context of religious life in contemporary Indonesia. Hikayat Nabi Isa holds significant value and strength in introducing, teaching, and deepening the understanding of Islamic teachings to the community, hence it is crucial to explore it. This research employs a descriptive-qualitative method. The primary data source is the manuscript of Hikayat Nabi Isa from the collection of the National Library of France with the code Malayo-Polynesien 68. The manuscript is transliterated and then utilized as the research object. A textual approach is employed in this research. Data are gathered through literature review techniques. Data processing involves stages of description, analysis, and evaluation. The findings of Islamic values and moralities within the text of Hikayat Nabi Isa encompass three aspects. Firstly, the connection between humans and Allah. Secondly, ethics and morality in society. Thirdly, the wisdom of human life's sagacity.